2013
DOI: 10.1007/s00216-013-7080-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymers as synthetic receptors for the QCM-D-based detection of l-nicotine in diluted saliva and urine samples

Abstract: Molecularly imprinted polymers (MIPs) are synthetic receptors that are able to specifically bind their target molecules in complex samples, making them a versatile tool in biosensor technology. The combination of MIPs as a recognition element with quartz crystal microbalances (QCM-D with dissipation monitoring) gives a straightforward and sensitive device, which can simultaneously measure frequency and dissipation changes. In this work, bulk-polymerized L-nicotine MIPs were used to test the feasibility of L-ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…To correct for the non-specific binding effect the normalized R th of the NIP was subtracted from the R th of the MIP. Previous research [15,17,23] has indicated that this operation facilitates the transition from well controlled buffer solutions to biological samples, such as urine, saliva or blood. Furthermore, external factors such as fluctuations of the environmental temperature, can be cancelled out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To correct for the non-specific binding effect the normalized R th of the NIP was subtracted from the R th of the MIP. Previous research [15,17,23] has indicated that this operation facilitates the transition from well controlled buffer solutions to biological samples, such as urine, saliva or blood. Furthermore, external factors such as fluctuations of the environmental temperature, can be cancelled out.…”
Section: Resultsmentioning
confidence: 99%
“…A novel read-out technique has been proposed to detect small organic molecules and cells with MIP type receptors [23,24]. This heat-transfer method (HTM) eliminates the need of sophisticated equipment since it requires only two thermocouples, a proportional-integral-derivative (PID) controller, an adjustable heat source, and ensures fast detection of a variety of target molecules in buffer solutions.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies linking the use of the Quartz Crystal Microbalance (QCM) to the detection of diseases characterizing biological fluids as blood [12,13,14,15], urine [16,17], saliva [17,18,19] and synovial fluid [20,21]. The methods proposed in these studies have proven to be successful according to their results.…”
Section: Introductionmentioning
confidence: 99%
“…Alenus et al have published two different studies on the detection of l -nicotine. One of the studies is in aqueous solution [26] while the other one is in a biological sample [27]. Although many researchers have studied l -nicotine template molecules in aqueous solution, Alenus et al studied the detection of l -nicotine in saliva and urine.…”
Section: Mip Based-quartz Crystal Microbalance (Qcm) Sensorsmentioning
confidence: 99%